From Prussia with love the George Muller story - Purves, Carol (Leominster, UK Day One, 2005)
Contents : A tear-away Prussian lad -- Pining in prison -- Missionary to where? -- Introduction to England -- West country witness -- An increasing workload -- The Brethren movement -- Orphans abound -- The Scriptural knowledge institution -- Moving times -- A million and a half in answer to prayer -- Onward and upward -- Home comforts -- Family matters -- Extending horizons -- Meeting at Mentone and other travels -- Aged travellers -- Last days -- But not the end-the work carries on. Includes bibliographical references, time line, photographs.
Keywords: Muller, George, -- 1805-1898; Brethren movement -- home workers -- biography; Brethren movement -- orphanages -- Great Britain; Brethren movement -- faith workers -- biography